Recursos didácticos multimedia para el aprendizaje de fuerzas y leyes de Newton en estudiantes del primer año de Bachillerato General Unificado - Armijos Rivas, Viky Silvana (2023)
The main objective of this research was to determine the importance of multimedia teaching resources in Physics learning in first-year students of the Unified General Baccalaureate. For this research, a descriptive investigation with a mixed approach was settled. Also, the qualitative approach was used to seek the conceptual information of the different categories of this study. Moreover, the quantitative one was developed in the field study. The empirical method was used, as well as the document review. The information was gathered by instruments such as; research logs, content sheets, and surveys addressed to students. The main results indicated that it is appropriate to use multimedia didactic resources for learning Physics since they facilitate the assimilation, reflection, and understanding of contents. At last, it was established that resources such as presentations, videos, infographics, and questionnaires are the most favorable for strengthening students' learning. Keywords: Multimedia teaching resources, multimedia, Physics, Newton's laws.